Transformation of Religious Moderation Awareness among Padang State University Students through Field Study–Based Experiential Learning - Rido Putra; Cici Nopriza; Firly Nazilah Putri; Feni Yulianti; Viona Dwi Wulandari (Universitas Islam Negeri Imam Bonjol Padang, 2026)
This study aims to examine the transformation of religious moderation awareness among Islamic Religious Education students at Padang State University (UNP) through the implementation of field study-based learning experiences at Multi-Religious Houses of Worship in Padang City. This study uses a qualitative approach with a phenomenological research type. Data collection was carried out through participant observation, in-depth interviews, documentation, and open-ended questionnaires as supporting instruments. The results of the study indicate: First, deconstructing prejudice through experiential learning has proven effective in deconstructing religious stereotypes attached to students due to their past social constructions. Through direct involvement and interaction with different religious communities, an inclusive religious paradigm is born, where students realize that diversity is not a threat, but rather a reality that must be managed moderately without obscuring the identity of each individual's beliefs. Second, the transformation of students' understanding from theoretical knowledge to existential awareness in religious moderation can be achieved effectively through the field study method. Third, the field study serves as a structured pedagogical process to strengthen cross-cultural and religious literacy and increase religious moderation among students. Theoretically, these findings strengthen and enrich Kolb's experiential learning and Mezirow's transformative learning models in the context of religious moderation education, by demonstrating that the transformation of students' religious awareness proceeds through systematic stages, starting from cognitive disorientation, critical reflection, and finally a permanent change in perspective. These theoretical implications emphasize the importance of integrating direct field experience as a core component in designing religious moderation curricula in higher education, not merely as a complement to theoretical learning in the classroom. The results of this study are expected to contribute to suppressing the trend of religious intolerance in Indonesia through the development of a multicultural experiential education model. Penelitian ini bertujuan untuk mengkaji transformasi kesadaran moderasi beragama pada mahasiswa Pendidikan Agama Islam Universitas Negeri Padang (UNP) melalui penerapan pengalaman belajar berbasis studi lapangan ke Rumah Ibadah Multi-Agama di Kota Padang. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian fenomenologi. Pengumpulan data dilakukan melalui observasi partisipatif, wawancara mendalam, dokumentasi, serta angket terbuka sebagai instrumen pendukung. Hasil penelitian menunjukkan. Pertama, dekonstruksi prasangka melalui experiential learning terbukti efektif dalam mendekonstruksi stereotip keagamaan yang melekat pada mahasiswa akibat konstruksi sosial masa lalunya. Melalui keterlibatan dan interaksi langsung dengan komunitas agama yang berbeda, melahirkan paradigma keberagamaan yang inklusif, di mana mahasiswa menyadari bahwa keberagaman bukanlah ancaman, melainkan realitas yang harus dikelola secara moderat tanpa perlu mengaburkan identitas keyakinan masing-masing. Kedua, Transformasi pemahaman mahasiswa dari pengetahuan teoretis menuju kesadaran eksistensial dalam moderasi beragama dapat dicapai secara efektif melalui metode studi lapangan. Ketiga, studi lapangan berfungsi sebagai proses pedagogis yang terstruktur untuk memperkuat literasi lintas budaya dan agama serta meningkatkan moderasi beragama di kalangan mahasiswa. Secara teoritis, temuan ini memperkuat sekaligus memperkaya model experiential learning Kolb dan transformative learning Mezirow dalam konteks pendidikan moderasi beragama, dengan menunjukkan bahwa transformasi kesadaran keagamaan mahasiswa berlangsung melalui tahapan secara sistematis, mulai dari disorientasi kognitif, refleksi kritis, hingga perubahan perspektif yang menetap. Implikasi teoritis ini menegaskan pentingnya mengintegrasikan pengalaman lapangan langsung sebagai komponen inti dalam desain kurikulum moderasi beragama di perguruan tinggi, bukan sekadar pelengkap dari pembelajaran teoretis di kelas. Hasil penelitian ini diharapkan berkontribusi dalam menekan tren intoleransi beragama di Indonesia melalui pengembangan model pendidikan berbasis pengalaman multikultural.